DETERMINAN KUALITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN TEKNOLOGI INFORMASI SEBAGAI PEMODERASI DI KOTA SIBOLGA - Kinanti Purnama Pasaribu; Afrah Junita; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2023)
With this research, we can find out the effect of the application of accrual basis SAP and HR capacity on the quality of local government financial reporting and information technology as a moderating variable in Sibolga City. Saturated sampling is used as a method that makes research easier and faster where the entire population is used as a sample. The number of samples in this study were 30 SKPD and data collection was carried out using a questionnaire. Based on the results of the study, the regression equation Y = 25.786 -4.404 X1 + 4.405 X2 + 0.421 M + 0.119 X1. M -0.111 X2.M + e in this equation there is a regression coefficient that is -0.111, this explains that there is a negative influence between HR capacity and information technology as a moderating variable which means that if HR Capacity with Information Technology as a moderating variable decreases, the quality of financial reporting local government will decrease by 0.111. The phenomenon studied is that several problems were found in the preparation of LKPD which were not in accordance with the SAP regarding the transfer of budget functions in the Sibolga city financial reports for the 2020 fiscal year. The results of the study show that one by one both the application of accrual-based government accounting standards and HR capacity affect the quality of local government financial reporting, with the use of information technology can strengthen the influence between the application of accrual-based SAP, and HR capacity on the quality of regional government financial reporting. Overall, the existence of Information Technology can strengthen the influence between the application of accrual basis SAP and HR Capacity on the quality of PEMDA financial reporting.